1999
DOI: 10.1093/ps/78.11.1493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amino acid injection in broiler breeder eggs on embryonic growth and hatchability of chicks

Abstract: Two experiments were conducted to evaluate the effect of amino acid (AA) injections in ovo in Cobb broiler breeder eggs on hatchability and subsequent chick BW. In Experiment 1, moisture, crude fat (CF), and CP were analyzed over time during incubation (Day 0, 7, 14, and 19 of incubation). Moisture, CP, and CF of the embryo increased, and moisture, CP, and CF of eggs decreased, as incubation time increased (P < 0.05). Combined egg and embryo AA contents, except Gly and Pro, decreased (P < 0.05) as incubation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
108
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 11 publications
8
108
0
6
Order By: Relevance
“…In our study BCAA injected into the amnion, yolk sac or albumin at 18 d of incubation did not, however, reduce hatchability or studied performance characteristics of birds. The disappearance between our study and previous studies (Al-Murrani, 1982;Ohta et al, 1999Ohta et al, , 2001) may be resulted in injection time (7 th vs. 18 th day of incubation), as reported by Bhanja and Mandal (2005). The albumen is transferred into the amniotic cavity and yolk sac (Ohta et al, 1999) after the second week of incubation.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…In our study BCAA injected into the amnion, yolk sac or albumin at 18 d of incubation did not, however, reduce hatchability or studied performance characteristics of birds. The disappearance between our study and previous studies (Al-Murrani, 1982;Ohta et al, 1999Ohta et al, , 2001) may be resulted in injection time (7 th vs. 18 th day of incubation), as reported by Bhanja and Mandal (2005). The albumen is transferred into the amniotic cavity and yolk sac (Ohta et al, 1999) after the second week of incubation.…”
Section: Resultssupporting
confidence: 61%
“…Hatchability and body weight at hatch may affect in ovo amino acid injection depending on injection site. Previous studies demonstrated that in ovo amino acid injection at 7 d into the yolk (Al-Murrani, 1982), air cell (Ohta et al, 1999), chorioallantoic membrane or into the amniotic cavity (Ohta and Kidd, 2001) decreased hatchability. In our study BCAA injected into the amnion, yolk sac or albumin at 18 d of incubation did not, however, reduce hatchability or studied performance characteristics of birds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has been shown that embryos survived after in-ovo injection of amino acids into the yolk (Al-Murrani, 1982) with little impacts on hatchability percentage (Hajihosaini and Mottaghitalab, 2004;Ohta et al, 1999 and. Inovo injection of 0.50 ml (84%) but not 0.75 ml of AA mixture (68%) into the yolk of fertilized Muscovy duck's eggs at the 12 th day of incubation increased hatchability percentage compared to the un-injected control (74%) and D.W injected groups (72%).…”
Section: Resultsmentioning
confidence: 99%
“…Hatched chicks are affected by the nutrients in the yolk remaining in the peritoneal cavity post-hatching (Romanoff, 1960). Nowadays, in ovo-injection is widely used for many purposes, such as fertilizing an avian egg in the shell (Cantrell and Wooten, 2003), injecting avian eggs with immunological material (Jochemsen and Jeurissen, 2002), a trial for sex reversal in birds (Kagmi and Hanada, 1997), increasing the post-hatching body weights of birds by in-ovo injection of growth promoters (Ohta et al, 1999), and enhancing the growth of avian embryo by injecting eggs with special liquid nutritional supplements. Nutrients in-ovo injection has a lot of benefits: greater efficiency of feed utilization (Bhanja et al, 2004); reduced post-hatch mortality and morbidity; improved immune response (Gore and Qureshi, 1997); enhanced early growth by improving intestinal function and development (Tako et al, 2004); and increased skeletal growth (Hargis et al, 1989), breast muscle yield (Hajihosaini and Mottaghitalab, 2004), and marketing body weight (Selim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%